Fetal Adrenal Hemorrhage with Prolonged Pregnancy: A Case Report - Gürhan Güney; Aytekin Tokmak; Ali İrfan Güzel; Aydan Sezer Kara; Melike Doğanay (Gynecology Obstetrics & Reproductive Medicine)
Fetal adrenal hemorrhage is a very rare clinical condition during pregnancy. There is limited data about this subject in antepartum period. With the widespread use of the obstetrical ultrasound, detection of fetal abdominal masses has become more common. In this case report we presented a case of pregnant woman (41w6d) with a fetus who had intraabdominal mass at right adrenal region.